Resistance Candida spp. for amphotericin B in cancer patients - N. S. Bagirova; N. V. Dmitrieva (Журнал инфектологии)
We have tested 253 strains (13 species) Candida spp. Determination of the minimum inhibitory concentration of amphotericin B was performed by 2 methods: epsilometric method (Etest®, BioMerieux, France) and on the instrument the Vitek2 (BioMerieux, France). In general, resistance was detected in 5 strains (2.1%) (C. parapsilosis – 4, C. tropicalis – 1). There were no resistance to amphotericin B among strains of C. albicans, C. glabrata and C.krusei. Coincidence evaluation results of the minimum inhibitory concentration of amphotericin B for categories sensitivity/resistance when tested strains 2 methods generally occurred in 98% of cases (248 of 253): 100% for the species C. albicans, C. glabrata and C.krusei, 92.2% for C. parapsilosis and 95% for C. tropicalis. The results of our study demonstrate a low degree of resistance of Candida spp. to amphotericin B, which allows the use of the drug in a